ANALISIS TRANSPARANSI DAN AKUNTABILITAS LAPORAN KEUANGAN ORGANISASI NIRLABA PANTI ASUHAN AL-MAUN DESA NGAJUM KABUPATEN MALANG - Budi Prihatminingtyas; Whinny Qori Fatima; Livia Khairunisa (Unitri Press, 2021)
The purpose of this study was to explained the management and conformity of the report with PSAK No. 45 and the accountability and transparency of the financial statements of the Al-Maun Orphanage. This research used descriptive qualitative research. The results showed that financial management was still relatively simple, because it came from infaq, sodaqoh and regular donors. According to the contract between the donor and the orphanage, the financial statements were also not in accordance with PSAK No. 45, because the financial statements only limited to cash income and expenditure, besides that they were not yet classified as accountable, due to the lack of understanding of the orphanage manager about financial management, but it is classified as simple transparent, because the financial statements of the orphanage were only given to those who want to know about the financial statements at the orphanage.